Respuesta :

Answer: [tex]YA=7x-1[/tex]

Step-by-step explanation:

You know that "Z" is the midpoint of "YA". This means the following:

[tex]YZ+ZA=YA[/tex]

Now, you know that the expression for "YZ" is:

[tex]YZ = x + 12[/tex]

And the given expression for "ZA" is:

[tex]ZA = 6x - 13[/tex]

Knowing these expressions, you can substitute them into [tex]YZ+ZA=YA[/tex], as following:

[tex]( x + 12)+(6x - 13)=YA[/tex]

Finally, you must add these expressions in order to get "YA".

Therefore, this is:

[tex]x + 12+6x - 13=YA\\\\7x-1=YA\\\\YA=7x-1[/tex]

ACCESS MORE